THE QUALITY TEST OF CHOCOLATE DRINK WITH THE ADDITION OF RED GINGER POWDER (ZINGIBER OFFICINAL) AND CINNAMON (CINNAMOMUM VERUM) (Jurnal Teknologi Industri Pertanian, 2024)
This study explored the medicinal properties of red ginger and cinnamon in chocolate beverage production. Red ginger, known for its traditional healing properties, and cocoa flavonoids, offering various health benefits, were combined to create a chocolate drink. Cinnamon, with its tannins and flavonoids, complements the mixture and is believed to stimulate blood circulation and provide a warming effect. The research aimed to identify the optimal formulation with varying red ginger-to-cinnamon ratios and assessed their influence on chocolate drink quality. Three ratios (95%:5%, 85%:15%, 75%:25%) were examined for water content, sucrose content, and organoleptic attributes. A Completely Randomized Design with three replications and post hoc testing using the Least Significant Difference was employed for data analysis. The best results were achieved with a 75% red ginger to 25% cinnamon ratio, scoring 3.41 (somewhat liked) in the aroma. Water and sucrose contents met Indonesian National Standards (01-4329-1996). In conclusion, the study underscores the positive effects of red ginger and cinnamon in chocolate drinks. The 75%:25% ratio yielded optimal aroma scores, meeting quality standards and providing insights for product development. This research contributes to understanding the impact of red ginger and cinnamon ratios on chocolate beverage characteristics.Keywords: red ginger powder, cinnamon powder, chocolate drink